Небо с овчинку: повести / М. С. Серова - Серова Марина Сергеевна (Эксмо, 2003)
Экземпляры: ф.8 (20180105) / Инвентарный номер: 35637 / Цена: 40.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 32 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6